Characterization of murine monoclonal antibodies to the tat protein from human immunodeficiency virus type 1. - Brake, D A (1990)
A panel of murine monoclonal antibodies (MAbs) to the human immunodeficiency virus type 1 trans-activator tat protein were characterized. The anti-tat MAbs were mapped to the different domains of the tat protein by Western blot (immunoblot) and Pepscan analyses. One-half of the MAbs tested mapped to the amino-terminal proline-rich region, and one-third of the MAbs tested mapped to the lysine-arginine-rich region of tat. The individual MAbs were tested for inhibition of tat-mediated trans activation, using a cell-based in vitro assay system. MAbs which mapped to the amino-terminal region of the tat protein demonstrated the highest degree of inhibition, whereas MAbs reactive to other portions of the molecule exhibited a less pronounced effect on tat function.